The military civil triennium: Córdoba (1943-1946) (Estudios Sociales, 2019)
This article offers a historiographic reconstruction of the period 1943-46 in the province of Córdoba, from an analytical perspective that contemplates four dimensions: the geographic centralization of authority in the National Executive Branch, its functional concentration in the Provincial Executive Branch, the practices of social control and the links of the State with the diverse actors of Cordoba society. Three hypotheses are explored in relation to these aspects. The first, refers to a double process of functional concentration of authority: in the national executive power to the detriment of provincial powers and in the provincial executive powers to the detriment of municipal governments. The second alludes to the ideological universe in which this process of concentration of political power was inscribed, marked by the pre-eminence of anti-liberal and authoritarian values. The third shows the systematic character of the repression, functional both to clericalism and to the nascent Peronism in their dispute for the control of the workers' movement.
Keywords: concentration of power; politica centralization; clericalism; peronism